Design of automatic hand sanitizer with ultrasonic sensor. Issue 1 (December 2020) - Lesmana, Jonathan; Halim, Agus; Purna Irawan, Agustinus
Abstract: An automatic hand sanitizer allows the discharge of the sanitizing liquid without pressing any nozzle. The design of the automatic hand sanitizer is focused on the mechanism of pressing the nozzle of the hand sanitizer that involves conversion from a rotation movement into a translation movement. VDI 2221 method is used to design the automatic hand sanitizer, which uses Arduino Nano as the microcontroller, servo motor as the motor, ultrasonic sensor for detecting the movement from the environment, and rack and pinion system as the mechanism for pressing the nozzle from the hand sanitizer. The prototype of automatic hand sanitizer has worked well and has become a reference for further development.